On algorithmization and automation of regional strategizing - Dubrovskaya Yu.V. (Ural State University of Economics, 2019)
Widespread digitalization of economy results in automation of management processes in both the industrial sector and the service sector, including public services. The paper examines the possibilities and prospects for algorithmization and automation of regional strategizing on the basis of identification of enterprises as potential participants of industry value chains within the promising economics specializations of the subjects of the Russian Federation. The methodological basis of the study embraces the theoretical and practical provisions of regional management and the system of modern specialized geographic information platforms in the field of territorial strategizing. The study involves a wide range of quantitative and qualitative methods of analysis; Python and JavaScript are used to automate the process of regional strategizing. Based on the innovative method for identifying enterprises – potential participants in industry value chains, the authors created a specialized web application. It not only automates the strategizing of regional development in terms of determining the priority areas for cooperation between business entities within the promising sectors of a region’s economic specialization, but also allows visualizing a given algorithm and the results of identification in the form of a geographical map. The developed web-application can become a powerful tool for automating the process of regional strategizing. This proves the necessity to perform further research on improving and enhancing the functionality of the software product.